Birds of Summer Solstice: World-Renewal Rituality on the Northern Gulf Coast of Florida. Issue 2 (May 2020) - Goodwin, Joshua M.; Sassaman, Kenneth E.; Blessing, Meggan E.; Steadman, David W.
Abstract : Prevalent as bird imagery is in the ritual traditions of eastern North America, the bony remains of birds are relatively sparse in archaeological deposits and when present are typically viewed as subsistence remains. A first-millennium ad civic-ceremonial centre on the northern Gulf Coast of Florida contains large pits with bird bones amid abundant fish bone and other taxa. The avian remains are dominated by elements of juvenile white ibises, birds that were taken from offshore rookeries at the time of summer solstices. The pits into which they were deposited were emplaced on a relict dune with solstice orientations. The timing and siting of solstice feasts at this particular centre invites discussion of world-renewal rituality and the significance of birds in not only the timing of these events but also possibly as agents of balance and rejuvenation.